Use of Oxygen Concentrators for Employees Recovering from Illness - Felixtianus Eko Wismo Winarto; Wiryanta Wiryanta (Jurnal Kesehatan Vokasional, 2025)
To increase the patient's blood saturated oxygen, an oxygen concentrator (OC) is needed. The way OC works is based on the process of air filtration and oxygen purification. Air enters an absorption column containing an absorbent such as molecular sieve (zeolite) or semipermeable membrane. In the absorption column, the air is separated into two main components: oxygen and nitrogen. Oxygen is collected and purified, while nitrogen and other components are removed.With this method of operation, OC can produce pure oxygen with high purity, which is suitable for use in the care of patients who need oxygen supplements. The main advantage of an oxygen concentrator is its ability to produce oxygen continuously.Individuals who have just recovered from illness usually have oxygen below 97, by using OC it can be increased to 99 or even 100 in less than 5 minutes. The average effectiveness of increasing saturated oxygen is 3% and the speed of increase is 2.01. While the number of heart beats per minute for each patient varies (average decrease of 9.15 points), the number of beats will decrease if the oxygen needs in the blood have been met, the patient feels comfortable. Most respondents feel helped by this OC, so continuous use is highly recommended to help their fitness.